Expressão da glicoproteína S1 do vírus da bronquite infecciosa das galinhas em sistemas procarioto e eucarioto para utilização em imunodiagnóstico - Finger, Paula Fonseca (2011)
The chickens infectious bronchitis (IB) is a highly contagious viral disease which causes predominantly respiratory lesions manifested clinically and invariably by sneezing and tracheo-bronchial rales, which may lead to more severe signs, with a decrease in fertility and reduction of eggs production. The infectious bronchitis virus (IBV) encodes four major structural proteins: N (nucleocapsid protein), S (spike protein), E (envelope protein) and M (membrane protein) being the S protein is cleaved into S1 and S2. The 1 subunit (S1) is found exposed in the viral envelope, which makes it an important or main inducer of neutralizing antibodies against the IBV, the main target for the host s immune system. The variations in two regions of the envelope s S1 subunit, called hypervariables regions, may originate to new serotypes. The IBV s mutation and recombination capacity and the selection pressure exerted by the prolonged use of live vaccines contribute to the appearance of a wide variety of serotypes and subtypes of IBV. The objective of this study was to express, in Pichia pastoris, the gene that encodes the surface protein S1 of IBV strain M41 and, in Escherichia coli, to express the S1 of the synthetic gene designed from consensus sequences of national and international field samples, as an interesting alternative for the production of antigen that can be used for monitoring vaccination of birds and also an antigen that is suitable for the use in serological diagnostic. The cloning and expression of glycoprotein S1 in both heterologous expression systems was successfully performed. The process of expression using E. coli was simple and quick when compared to the use of P. pastoris. The P. pastoris was able to express the entire S1; however, it showed difficulty in secreting the glycoprotein. The results will be evaluated for use in immunodiagnostic kit for monitoring the disease in poultry, being more affordable than the ones existing currently.